Impact of Invasive Weeds on the Diversity and Dissimilarity of Bird Communities in Forested Areas - Emilia Grzędzicka (Diversity, 2022)
Caucasian hogweeds, mainly the Sosnowsky’s hogweed Heracleum sosnowskyi and the giant hogweed Heracleum mantegazzianum, create one of the most problematic plant invasions in the world. Due to their large size (weeds reaching 4–5 meters in height), they seem to be herbaceous plants that can threaten birds living in forest stands. This research quantified the structure and diversity of the forest birds’ community in forests with varying areas of invasive hogweeds located in south-eastern Poland. Changes in the accompanying non-forest birds’ community were also assessed. The study addressed the following questions: 1. How does the invaded area correlate with the abundance of forest birds? 2. How do communities and species respond to invaded vegetation? 3. How do the invading plants affect the various types of diversity of forest and non-forest birds? It turned out that both surveyed bird communities had a lower alpha diversity in invaded sites. Only forest birds, not able to change their location easily, formed a unique community (i.e., had a higher beta diversity) near invaders. Forest birds showed unchanged functional diversity based on the relative bird abundance and their connection, or lack of it, with the forest development phases. The effect of hogweeds on the abundance of forest birds was more negative in severely invaded areas with anthropogenic habitats. Non-forest birds showed higher species loss near the invasion, constant beta diversity and decreased functional diversity. This study is important as the forest is a climax community in the temperate zone, and unused open areas become spontaneously overgrown with young forests. Weeds disseminating after crop abandonment can highly and commonly affect forest and non-forest bird communities co-occurring in this type of overgrowing area.